Efficacy and initial dose determination of paricalcitol for treatment of secondary hyperparathyroidism in Chinese subjects - Yan, Yucheng; Qian, Jiaqi; Chen, Nan; Huang, Zhaoxing; Jiang, Gengru; Li, Xuewang; Lin, Hongli; Liu, Liqiu; Wang, Mei; Xing, Changying; Yu, Xueqing; Zuo, Li; et al. (Clinical nephrology, 2014)
Prevalence of secondary hyperparathyroidism (SHPT), a renal disease complication, is increasing in China. Available therapies may not optimally control SHPT, particularly in patients with hypercalcemia, hyperphosphatemia, and parathyroid hyperplasia. This study examined efficacy and safety of two dosing regimens of selective vitamin D receptor activator paricalcitol. Subjects with SHPT (n = 216) undergoing hemodialysis were treated with paricalcitol i.v. for 12 weeks. One group was treated according to the EU paricalcitol package insert (PI) (initial μg dose based on iPTH/80), and the other was treated according to the US PI (initial dose of 0.04 μg/kg). Dose titration was based on iPTH and serum calcium (Ca) and phosphorus (P) levels. The primary endpoint of two consecutive ≥ 30% iPTH decreases was achieved by 88.6% and 55.9% of subjects in the EU and US PI groups, respectively. Noninferiority of the EU PI group vs. the US PI group was demonstrated (lower bound of the 1-sided 97.5% CI = 21.3%). Superiority of the EU PI group was shown (lower limit > 0%) and confirmed by Fisher's exact test (p < 0.001); both groups showed similar achievement of recommended KDIGO iPTH levels. Ca and P levels were relatively constant. Both EU and US PI paricalcitol dosing strategies effectively reduced iPTH levels in Chinese subjects with SHPT, with minimal impact on Ca and P levels.